2018
DOI: 10.1038/s41467-018-07162-5
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity and network state-dependent recruitment of long-range VIP-GABAergic neurons in the mouse hippocampus

Abstract: GABAergic interneurons in the hippocampus provide for local and long-distance coordination of neurons in functionally connected areas. Vasoactive intestinal peptide-expressing (VIP+) interneurons occupy a distinct niche in circuitry as many of them specialize in innervating GABAergic cells, thus providing network disinhibition. In the CA1 hippocampus, VIP+ interneuron-selective cells target local interneurons. Here, we discover a type of VIP+ neuron whose axon innervates CA1 and also projects to the subiculum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 72 publications
3
105
0
Order By: Relevance
“…Given that here the soma size of VIP+ cells recorded in vivo was used for pIS3 identification and that all CR+/VIP+ cells have a smaller soma size ( Figure 5), the subiculum-projecting fraction of this population could be sampled as pIS3 cells and contribute to variability in cellular activity patterns. Indeed, we reported that the subiculum-projecting VIP+ cells are the theta-off cells, as they strongly decrease their activity during theta-run episodes [32]. The latter was seen in a small number of pIS3 cells recorded in the current study (3/18 cells were decreasing activity during theta-run episodes), and may be due to specific modulatory inputs received by the two VIP+ cell types.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…Given that here the soma size of VIP+ cells recorded in vivo was used for pIS3 identification and that all CR+/VIP+ cells have a smaller soma size ( Figure 5), the subiculum-projecting fraction of this population could be sampled as pIS3 cells and contribute to variability in cellular activity patterns. Indeed, we reported that the subiculum-projecting VIP+ cells are the theta-off cells, as they strongly decrease their activity during theta-run episodes [32]. The latter was seen in a small number of pIS3 cells recorded in the current study (3/18 cells were decreasing activity during theta-run episodes), and may be due to specific modulatory inputs received by the two VIP+ cell types.…”
Section: Discussionsupporting
confidence: 45%
“…CA1 PCs or subcortical neuronal populations), or cellular diversity within the pIS3 cell population. Indeed, we recently identified a new type of VIP+ long-range projecting (VIP-LRP) cell in the CA1 hippocampus that, in addition to the CA1, innervates subiculum with a region-specific target preference [32]. Further diversity was revealed within the VIP-LRP population, with cells co-expressing the muscarinic receptor 2, CR or proenkephalin in addition to VIP, and having somata located within PYR, RAD or LM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence suggests that disinhibitory circuits play a crucial role in various cognitive tasks such as fear conditioning (Letzkus et al, 2011;Pi et al, 2013) and sensory discrimination (Hangya et al, 2015;Pinto et al, 2013). The dominant interneuron types of the disinhibitory circuits are VIP, SOM and PV inhibitory neurons (Donato, Rompani, & Caroni, 2013;Francavilla et al, 2018;Kamigaki & Dan, 2017;S. Zhang et al, 2014).…”
Section: Dynamic Processing Across Multiple Areasmentioning
confidence: 99%